2012
DOI: 10.1002/jnr.23161
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in local thyroid hormone signaling in the hippocampus of the SAMP8 mouse at younger ages: Association with delayed myelination and behavioral abnormalities

Abstract: The senescence-accelerated mouse (SAM) strains were established through selective inbreeding of the AKR/J strain based on phenotypic variations of aging and consist of senescence-prone (SAMP) and senescence-resistant (SAMR) strains. Among them, SAMP8 is considered as a model of neurodegeneration displaying age-associated learning and memory impairment and altered emotional status. Because adult hypothyroidism is one of the common causes of cognitive impairment and various psychiatric disorders, we examined the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
25
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(31 citation statements)
references
References 43 publications
5
25
0
1
Order By: Relevance
“…SAMP8 mice showed reactive astrocytes in the hippocampus. Previous authors have demonstrated that the number of astrocytic cell bodies remained constant with age in the SAMP8 hippocampus despite increased GFAP immunoreactivity, thus indicating a change in hypertrophic reactivity (Sawano et al, 2013). SAMP8 reactive astrocytes appear to play a significant role in exaggerated and long-lasting brain inflammatory responses against stress factors and subsequent impairment of memory in SAMP8.…”
mentioning
confidence: 90%
See 1 more Smart Citation
“…SAMP8 mice showed reactive astrocytes in the hippocampus. Previous authors have demonstrated that the number of astrocytic cell bodies remained constant with age in the SAMP8 hippocampus despite increased GFAP immunoreactivity, thus indicating a change in hypertrophic reactivity (Sawano et al, 2013). SAMP8 reactive astrocytes appear to play a significant role in exaggerated and long-lasting brain inflammatory responses against stress factors and subsequent impairment of memory in SAMP8.…”
mentioning
confidence: 90%
“…Motor activity and ambulation was tested in both mouse strains to discard any local effect of the vector injection. Furthermore, SAMP8 mice are reported to display non-cognitive alterations, such as sensorimotor impairment, hyperactivity, and reduced anxiety-like behavior compared with SAMR1 (Markowska et al, 1998;Miyamoto et al, 1992;Sawano et al, 2013). These non-cognitive behaviors were also tested for proinsulin-induced changes.…”
Section: Proinsulin Protected Against Cognitive Deficits In Samp8 Micementioning
confidence: 99%
“…Using SAM/resistant-1 (SAMR1) as a control, the senescence accelerated mouse prone-8 (SAMP8) is a robust model of AD because it shares phenotypes that resemble the symptoms of late-onset and age-related sporadic AD patients and because has distinct advantages over the gene-modified model (Pang et al, 2006; Pallas et al, 2008; Woodruff-Pak, 2008; Tomobe and Nomura, 2009; Morley et al, 2012; Pallàs, 2012). Although investigators have developed new therapies and have tested in detail, the structural (Gutierrez-Cuesta et al, 2007; del Valle et al, 2012; Li et al, 2012), functional (Sureda et al, 2006; Tajes et al, 2008; Lou et al, 2012; Yamaguchi et al, 2012) and behavioral consequences (Gong et al, 2008; Shi et al, 2010b; Shih et al, 2010; Chang et al, 2012; Kanno et al, 2012; Lopez-Ramos et al, 2012; Lou et al, 2012; Orejana et al, 2012; Dobarro et al, 2013; Huang et al, 2013; Sawano et al, 2013) of AD-associated pathology based on SAMP8 mice, little progress has been made with regard to the patho-physiological mechanisms of SAMP8 mice, and the underlying causes of the AD-like phenotype in SAMP8 mice remain unknown.…”
Section: Introductionmentioning
confidence: 99%
“…In spite of normal serum TH levels, TH signaling in the SAMP8 hippocampus was thus significantly attenuated as monitored by the reduction in the expression of typical TH‐dependent genes (Sawano et al . ).…”
mentioning
confidence: 97%